Bally - A History of Footwear in the Interwar Period - Herm, Henriette-Friederike; Schlittler, Anna-Brigitte; Schlittler, Anna-Brigitte; Späti, Daniel; Tietze, Katharina; Tietze, Katharina; Wild, Roman (2021)
Carl Franz Bally founded a shoe factory in Switzerland in 1851. Within decades, the Bally name had achieved worldwide recognition for its high-quality footwear. The history of modern footwear can be traced through the lens of Bally's corporate evolution. This book brings together the results of research on such topics as the economic importance of fashion, Bally's fortunes in the US, the career of shoe design, the sourcing and use of materials, and the rise of strategic product display. The research focuses on the 1930s and 1940s: years of economic crisis and war, characterized by a wide diversity of designs and increasing variety in product range. Shortages also led to experiments with materials and technical innovations. Featuring numerous points of contact with adjacent fields of historical study, this publication marks a contribution to the history of fashion as the history of industrially manufactured products.